Job le juste, modèle de patience: au sujet du cycle de saint Antoine dans l'atrium de Sainte-Marie-Antique à Rome - Luisier, Philippe (Orientalia christiana periodica, 2024)
In the atrium of the church of Santa Maria Antica in Rome, there is a 10th-century cycle of paintings dedicated to the life of Saint Anthony. The frescoes are badly damaged, but a figure with a naked torso can still be clearly seen at the bottom left of a temptation scene, while his legs are clearly stretched out on the floor. This figure has been interpreted as Anthony, but we propose to recognise Job as the righteous man of the Old Testament, a model of patience and abandonment to the divine will. Apart from the Life of Anthony, the only homiletical and liturgical texts that associate the Father of the Monks with Job, come from the East, from Jerusalem to be precise: we may therefore ask ourselves how this Eastern tradition reached Rome at this time.